ChemInform Abstract: Simple Indole Alkaloids and Those with a Non‐Rearranged Monoterpenoid Unit. Issue 33 (25th July 2013) - Ishikura, Minoru; Abe, Takumi; Choshi, Tominari; Hibino, Satoshi
Abstract Review: 265 refs.